Links between tenure security and food security: Evidence from Ethiopia - Ghebru, Hosaena H.; Holden, Stein (International Food Policy Research Institute, 2013)
This study uses five rounds of household panel data from Tigray, Ethiopia, collected in the period 1998–2010 to assess the impacts of a land registration and certification program that aimed to strengthen tenure security and how it has contributed to increased food availability and, thus, food security in this food-deficit region. Results show that land certification appears to have contributed to enhanced calorie availability (calorie intake), and more so for female-headed households, either through enhanced land rental market participation or increased investment and productivity on owner-operated land. Results also show that members of households that accessed additional land through the land rental market had a significantly higher body mass index.